Glial Purinergic Signaling in Neurodegeneration - Pietrowski, Marie J.; Gabr, Amr Ahmed; Kozlov, Stanislav; Blum, David; Halle, Annett; Carvalho, Kevin (Frontiers in Neurology, 2021)
Purinergic signaling regulates neuronal and glial cell functions in the healthy CNS. In neurodegenerative diseases, purinergic signaling becomes dysregulated and can affect disease-associated phenotypes of glial cells. In this review, we discuss how cell-specific expression patterns of purinergic signaling components change in neurodegeneration and how dysregulated glial purinergic signaling and crosstalk may contribute to disease pathophysiology, thus bearing promising potential for the development of new therapeutical options for neurodegenerative diseases.